(untitled) (International Journal of Physiotherapy, 2017)
Background: Physiotherapists were at high risk of getting work-related musculoskeletal disorders. However, studies prevalence of work-related musculoskeletal disorders among clinical and teaching physiotherapists in India was limited. The objective of the study is to find the prevalence of work-related musculoskeletal disorders among clinical and teaching physiotherapists. Methods: Non-experimental design. 210 samples were taken applying both inclusion and exclusion criteria. The Nordic questionnaire was used to find the prevalence of work-related musculoskeletal disorders among clinical and teaching physiotherapists. Result: Neck region was affected more among both clinical and teaching physiotherapists at a rate of clinical- 62.4% and in teaching- 63.8%. Teaching physiotherapists were affected more than clinical physiotherapists. Followed by back region was affected.i.e. lower back was affected more than upper back at the prevalence of lower back- 61% and upper back - 51.8%.the prevalence of knee was next to back region at the percentage of 29.1% and in the sidewise left knee was affected more than right knee (left knee-12.1, right knee - 10.6% and both knees -6.4%). Conclusion: Therefore, the prevalence of work-related musculoskeletal disorders among both clinical and teaching physiotherapists were at a high rate.